PENERAPAN METODE MIKIR (MENGALAMI, INTERAKSI, KOMUNIKASI, REFLEKSI) BERBANTUAN MEDIA FLIPPITY DALAM PEMBELAJARAN MENULIS TEKS BIOGRAFI DI KELAS X SMAN 09 BANDUNG - Syaza Naurah Fatin; Any Budiarti; Adi Rustandi (STKIP Subang, 2024)
This research discusses the issue of writing biographical texts in Indonesian language lessons. In the Merdeka Curriculum, every learning achievement requires students' writing skills. The need for biographical text writing skills does not match the conditions of class X students at SMAN 9 Bandung. Indonesian language lessons are often considered boring by students, which is due to teachers still using outdated methods and media that do not follow modern developments. This study aims to determine: the writer's ability to design, implement, and evaluate biographical text writing lessons using the MIKIR method assisted by flippity media,the students' abilities before applying the MIKIR method assisted by flippity media,the students' abilities after applying the MIKIR method assisted by flippity media, the difference in students' abilities before and after applying the MIKIR method. With using a quantitative experimental design with a quasi-experimental design, the study found: 1) the writer was able to implement biographical text writing lessons using the MIKIR method with an average score of 4. 2) the condition of students before receiving the MIKIR method and flippity media. 3) the condition of students after receiving the MIKIR method and flippity media. 4) the difference in students' abilities before and after receiving the MIKIR method.This study aims to improve the writing skills of students in Indonesian language lessons by using the MIKIR method assisted by flippity media, which is expected to enhance students' engagement and motivation in learning.